2023
DOI: 10.1371/journal.pntd.0011399
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of Voltage-gated sodium channel (VGSC) gene mutations in Aedes albopictus (Diptera: Culicidae) suggest rapid insecticide resistance evolution in Shanghai, China

Abstract: Background Dengue fever is an infectious disease that is imported into Shanghai, China and requires prevention and control measures. Controlling the vector Aedes albopictus through insecticide use is a key approach to dengue control. However, the rapid evolution of insecticide resistance in Ae. albopictus has raised concerns about the failure of dengue control efforts. Knockdown resistance (kdr) caused by point mutations in the voltage-gated sodium channel (VGSC) gene is a primary mechanism of pyrethroid resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…One of the variants of F1534L requires 2 substitutions from the wild-type state. Heterozygote 1534C/1534S individuals have also been found in China ( Wei et al 2021 , Zheng et al 2022 , Yuan et al 2023 ) along with 1534L/1534S ( Liu et al 2020 , Wei et al 2021 ) and the first report of phenylalanine to isoleucine mutation appearing as a heterozygote with 1534S (1534S/1534I) ( Yuan et al 2023 ). Italy is another focal point for studies in this area and 9 Vssc mutations have been recorded from Ae .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the variants of F1534L requires 2 substitutions from the wild-type state. Heterozygote 1534C/1534S individuals have also been found in China ( Wei et al 2021 , Zheng et al 2022 , Yuan et al 2023 ) along with 1534L/1534S ( Liu et al 2020 , Wei et al 2021 ) and the first report of phenylalanine to isoleucine mutation appearing as a heterozygote with 1534S (1534S/1534I) ( Yuan et al 2023 ). Italy is another focal point for studies in this area and 9 Vssc mutations have been recorded from Ae .…”
Section: Resultsmentioning
confidence: 99%
“…Functional studies have confirmed a causative function of this allele to pyrethroid resistance ( Yan et al 2020 , Guo et al 2022 ). The detection of F1534S (TCC) in China, the United States, and possibly Vietnam is of concern, suggesting that this resistant genotype ( Chen et al 2016 , Xu et al 2016 , Gao et al 2018 , Li et al 2018 , Wei et al 2021 , Wu et al 2021 , Guo et al 2022 , Yuan et al 2023 ) is already spreading. A recent study by Chen et al (2021) included historical samples and revealed the presence of the F1534S mutation (TCC) in Ae .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations